Comparision of Caudal Ropivacaine, Ropivacaine Plus Ketamine and Ropivacaine Plus Fentanyl Administration for Postoperative Analgesia in Children - Singh, Jeevan; Hamal, Dikshya; Karmacharya, Avish (Journal of Nepal Paediatric Society, 2013)
Introduction: The purpose of the study was to compare the analgesic quality and duration of Ropivacaine 0.2% with the addition of Fentanyl (1 mcg/kg) with that of Ropivacaine 0.2% and the addition of Ketamine (0.5 mg/kg) and also compare the post complications. Materials and Methods: Ninety children, age one to ten years, undergoing sub-umbilical surgery, were prospectively randomized to one of three groups: caudal analgesia with 0.75 ml/kg of 0.2% Ropivacaine in normal saline (Group R) or caudal analgesia with 0.75 ml/kg of 0.2% Ropivacaine with Ketamine 0.5 mg/kg (Group RK) or caudal analgesia with 0.75 ml/kg of 0.2% Ropivacaine with Fentanyl 1 mcg/kg (Group RF). Post-operative pain was assessed for 24 hours using the FLACC scale. Results: The mean duration of analgesia was significantly longer in Group RK (629.06 ± 286.32 min) than other two groups P < 0.05. The pain score assessed using FLACC scale was compared between the three groups, and children in Group RK had lower pain scores, which was statistically significant. The requirement of rescue medicine was lesser in Group RK. Ketamine in a dose of 0.5 mg/kg added to 0.2% bupivacaine for caudal analgesia, during sub-umbilical surgeries, prolongs the duration of analgesia of Ropivacaine, without any side effects in compare to Ropivacaine alone or Fentanyl. Conclusion: We conclude that Ketamine in a dose of 0.5 mg/kg, added to 0.2% Ropivacaine for caudal analgesia and administered as a 0.75 ml/kg mixture in children, for sub-umbilical surgery, significantly prolongs the duration of post-operative analgesia without any side effects. DOI: http://dx.doi.org/10.3126/jnps.v32i3.6956 J. Nepal Paediatr. SocVol.32(3) 2012 210-215